2012
DOI: 10.3791/3883
|View full text |Cite
|
Sign up to set email alerts
|

Harvesting Murine Alveolar Macrophages and Evaluating Cellular Activation Induced by Polyanhydride Nanoparticles

Abstract: Biodegradable nanoparticles have emerged as a versatile platform for the design and implementation of new intranasal vaccines against respiratory infectious diseases. Specifically, polyanhydride nanoparticles composed of the aliphatic sebacic acid (SA), the aromatic 1,6-bis(p-carboxyphenoxy)hexane (CPH), or the amphiphilic 1,8-bis(p-carboxyphenoxy)-3,6-dioxaoctane (CPTEG) display unique bulk and surface erosion kinetics and can be exploited to slowly release functional biomolecules (e.g., protein antigens, imm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 16 publications
0
14
1
Order By: Relevance
“…The results showed that the number of eosinophil in the lung tissue did not increase in sensitized mice exposed to hematite NPs, arguing against a significant cellular translocation to the interstitial compartments. Regarding the second alternative, cellular migration from the airways to the LDLN, it has been well described that both macrophages and lymphocytes may migrate to this compartment (Kirby et al, 2009;Chavez-Santoscoy et al, 2012;Caucheteux et al, 2013;Pabst and Binns, 1995). However, we consider this to be unlikely in this study since the total cell number in the lymph nodes was reduced, similarly to the cellular reduction observed in the BALF.…”
Section: Discussioncontrasting
confidence: 62%
“…The results showed that the number of eosinophil in the lung tissue did not increase in sensitized mice exposed to hematite NPs, arguing against a significant cellular translocation to the interstitial compartments. Regarding the second alternative, cellular migration from the airways to the LDLN, it has been well described that both macrophages and lymphocytes may migrate to this compartment (Kirby et al, 2009;Chavez-Santoscoy et al, 2012;Caucheteux et al, 2013;Pabst and Binns, 1995). However, we consider this to be unlikely in this study since the total cell number in the lymph nodes was reduced, similarly to the cellular reduction observed in the BALF.…”
Section: Discussioncontrasting
confidence: 62%
“… 8 Therefore, murine AMs were isolated following BAL washes and cultured in vitro for 24 hours to generate an inflammatory phenotype, as previously described. 11 Culture-induced iAMs were identified as F4/80 + CD11c + CD11b + cells using flow cytometry (online supplementary figure 1A ). Although variable, the percentage of iAMs present after 24 hours of culture did not alter significantly between conditions (P=0.113; online supplementary figure 1B ).…”
Section: Resultsmentioning
confidence: 99%
“…Alveolar macrophages were isolated post mortem via the trachea in 10× 1 mL PBS BAL washes from male or female Pdpn fl/fl VAV1cre + and floxed-only control mice, aged 8–17 weeks, as previously described. 11 Cells were cultured for 24 hours either untreated or treated with 0.1 µg/mL LPS in the presence or absence of an α-PDPN (clone 8.1.1) (10 µg/mL). Secreted cytokines and chemokines were measured in the supernatant by Fluorokine MAP Multiplex (R&D Systems, Abingdon, UK).…”
Section: Methodsmentioning
confidence: 99%
“…Human peripheral blood monocytes (THP-1) cells (TIB-202; American Type Culture Collection, Manassas, VA, USA) were differentiated into macrophages by treatment with Phorbol 12-myristate 13-acetate (MilliporeSigma, Burlington, MA, USA) for 72 h. Mouse peritoneal macrophages were isolated from peritoneal cavities of 3% thioglycolate-injected mice 5 d after injection, during which time mice were exposed to room air or smoke (Reference Cigarette 3R4F; University of Kentucky) exposure conditions. Mouse alveolar macrophages were isolated from bronchoalveolar lavage fluid of mice exposed to 5 d of room air or smoke (31). Mouse BMDMs were obtained from LysMCreAbca1 flox/flox (ABCA1 KO) and Abca1 flox/flox (ABCA1 WT control) mice that were bred in a C57BL/6J background.…”
Section: Macrophage Cell Culturementioning
confidence: 99%